Peran Lingkungan Belajar dalam Mendorong Efektivitas dan Motivasi Belajar Matematika pada Jenjang SMP/Sederajat - Haerunisa, Ines; Maelani, Suci Anggi (Universitas Pendidikan Ganesha, 2025)
The role of the learning environment in the effectiveness and motivation of students is very important. Therefore, this study aims to find out how much the learning environment affects the effective mathematics learning process and can increase the motivation to learn mathematics in children or junior high school students/equivalent. This research was conducted using a descriptive quantitative method whose data was obtained from the collection of questionnaire data of junior high school students, especially in Kuningan district. This study focuses on students' perception of environmental indicator factors, such as the availability of teaching facilities, the climate in the classroom, teachers' explanations of the material, the support of teachers, friends and parents who they consider to have an influence on their understanding and achievement in learning mathematics. The findings of this study reveal that environment and support are the key to the effectiveness and motivation of students' mathematics learning